Referral reward programs with scarcity messages on bank credit card adoption. Issue 2 (28th February 2019) - Song, Chanho; Wang, Tuo; Hu, Michael Y.
Abstract : Purpose: The purpose of this paper is to investigate how referral reward programs (RRPs) with scarcity messages influence consumer' recommendation behavioral intentions about a bank credit card. Design/methodology/approach: In total, 1, 599 consumers are accessed through Amazon's Mechanical Turk worker panel. The authors use general linear models, analysis of variance and analysis of covariance to test the proposed hypotheses. Findings: The results showed that offering RRPs with scarcity messages increases a consumer's behavioral intentions to recommend. The limited-quantity message in RRPs has the highest positive impact on consumers' behavioral intentions. Originality/value: No prior studies have addressed the relationship between referral rewards and scarcity messages in the bank credit card context. The study contributes to the understanding of the effectiveness of RRPs with scarcity message in improving consumer's referral.